Mortality Risk Stratification Using Cluster Analysis in Patients With Myositis-Associated Interstitial Lung Disease Receiving Initial Triple-Combination Therapy - Gono, Takahisa; Masui, Kenichi; Sato, Shinji; Kuwana, Masataka (Frontiers in Medicine, 2022)
Objective: To stratify patients with polymyositis/dermatomyositis-associated interstitial lung disease (ILD) who were initially treated with an intensive regimen consisting of high-dose corticosteroids, a calcineurin inhibitor, and intravenous cyclophosphamide (triple-combo therapy) into subgroups based on mortality outcomes by a cluster analysis using a large-scale multicenter retrospective cohort of Japanese patients with myositis-associated ILD (JAMI). Methods: Two-step cluster analysis of preclustering and subsequent hierarchical clustering was conducted in 185 patients who received triple-combo therapy in an unbiased manner. Initial predictors for mortality previously reported in patients with myositis-associated ILD were used as variables and included age, sex, disease duration, classification of myositis, requirement of supplemental oxygen, anti-aminoacyl tRNA synthetase (ARS) antibody, anti-melanoma differentiation-associated gene 5 (MDA5) antibody, and serum levels of C-reactive protein (CRP) and Krebs von den Lungen-6 (KL-6). The cluster model was further applied to 283 patients who received conventional regimens consisting of corticosteroids with or without a single immunosuppressive agent (dual-combo therapy or monotherapy). Cumulative survival rates were compared using Kaplan–Meier analysis, and the log-rank test was used to test for significant differences between two groups. Results: We developed a cluster model consisting of 6 clusters, which were categorized by age at onset, clinically amyopathic dermatomyositis, CRP, KL-6, requirement of supplemental oxygen, anti-ARS antibody, and anti-MDA5 antibody. This model was judged to be of good quality based on the silhouette measure of cohesion and separation of 0.6. These clusters were regrouped into three subsets based on low (<10%), moderate (10-50%), and high (>50%) mortality rates. The performance of the clustering was generally replicated in patients who received initial dual-combo therapy or monotherapy. Survival benefits of triple-combo therapy over dual-combo therapy or monotherapy were not observed in any of the clusters. Conclusion: We successfully developed a cluster model that stratified patients with myositis-associated ILD who were treated with initial triple-combo therapy into subgroups with different prognoses, although this model failed to identify a patient subgroup that showed survival benefits from triple-combo therapy over dual-combo therapy or monotherapy.